Success Rate on Double-J Stenting on Gynecological Cancer Patients: A Meta-Analysis Study - Sitti Riri Hafsari; Setya Anton Tusara Wardaya (HM Publisher, 2021)
Background. Metastatic cervical cancer in the ureter may lead to obstructive uropathy due to mechanical ureteral blockage. The insertion of a double-J (DJ) stent is a urinary diversion option that can be offered to the patients, but it becomes challenging due to the high rate of failures. This study aim to analyze the success rate on DJ Stent placement on patients with gynecological malignancy. Methods. The study was a systematic review using medical journals collected from Google Scholar, BMJ and PubMed. The journals were searched from 2015 to 2020. The database search throughout 2015-2020 using “Double J Stent’, “Gynecological”, “Malignancy”, “Kidney failure”, “Hydronephrosis” and “Urethral Obstruction”. A literature search was performed and evaluated based on established criteria. The quality assessment of included studies done according to the PRISMA. Meta analysis were done using the fixed effect model or random effect model. Results. The identified article on each med were collected using Mendeley Desktop software. There were 101 scientific publication from PubMed, 232 from Scopus, 1 from Cochrane and 60 from reseachgate results found using the combined keywords. The total of 7 publications matched all the inclusion criteria in this study. Conclusions. Patient’s general well-being could be measured by the staging of the malignancies and kidney function laboratory test. Another factor should be think through was the side effects of the chemotherapy or radiotherapy, as well as the compliance of the patient during stent maintenance.